Physiology of Islet Engraftment - Kampf, C.; Carlsson, P- O. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2006)
Pancreatic islet transplantation is a tempting strategy to treat patients with type 1 diabetes mellitus, since if successful it could provide a cure for the disease. At present, there is, however, a poor long-term outcome of such transplantations compared to the results for whole pancreas transplantation. One explanation for this may be inadequate engraftment of the transplanted cells in the new microenvironment. The engraftment process includes immediate survival in the post transplantation phase. There is likely extensive cell death immediately following transplantation mainly due to inflammatory responses triggered by e.g. hypoxia. Also the long-term survival and function of the transplanted islets is encompassed by the term engraftment. This is influenced by the cellular turn-over rate, and the degree of revascularization and reinnervation of the islet tissue. To regain optimal function in surviving cells, new vascular and nervous systems similar to those in endogenous islets need to form. Both qualitative and quantitative changes compared to endogenous islets have, however, been described in the new vascular system that develops following transplantation, and these changes seem to have consequences for islet blood perfusion, metabolism and function. Comparatively little is known regarding the extent of functional re-growth of nerves that occurs, and its influence on graft function. This review also discusses the challenges of engraftment that seem specific for intraportally transplanted islets, e.g. the instant blood mediated immune reaction, the loss of glucagon response to hypoglycemia, and the lower β-cell proliferation rate in intraportally transplanted islets than in islets grafted to the kidney.
Keywords: liver